Exploring vernacular typography in the development of modern visual identity systems - Hamim Najib Fahmi; Gianjar Wasito Adi; Ainun Aulia Isnaini (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: This study examines how vernacular typography type forms rooted in local cultural, historical, and socio-visual traditions can be integrated into modern visual identity systems to create distinctive, culturally grounded brands. While contemporary identity design trends often prioritize minimalism and globalized aesthetics, recent research indicates a growing demand for culturally specific visual identities capable of fostering authenticity and emotional resonance among audiences. This paper investigates the visual, semiotic, and functional characteristics of vernacular typography found in Indonesian street signage, hand-painted lettering, traditional scripts, and local typographic artifacts. Methods: The study employs systematic photographic documentation of vernacular typography from diverse public environments, capturing the expressive, culturally embedded letterforms created by self-taught artisans. These artifacts are analyzed through visual semiotics, typographic structural analysis, and comparative identity evaluation to translate culturally authentic features into viable modern place branding and visual identity systems. Findings: The findings reveal that vernacular typographic features such as stroke modulation, spatial rhythm, ornamentation, and culturally embedded symbolisms can enhance brand distinctiveness when selectively adapted and standardized. Conclusion: This study proposes a design framework for integrating vernacular typographic cues into corporate and cultural branding practices, contributing to both the preservation of local visual heritage and the innovation of contemporary identity design. Novelty/Originality of this article: This article offers an original contribution by proposing a systematic design framework that translates vernacular typographic characteristics into scalable modern identity systems, positioning local visual heritage as a strategic resource for authentic and distinctive branding.